2017
DOI: 10.1186/s12917-017-1041-4
|View full text |Cite
|
Sign up to set email alerts
|

A robust PCR for the differentiation of potential virulent strains of Haemophilus parasuis

Abstract: Background Haemophilus parasuis is the etiological agent of Glässer’s disease in swine. H. parasuis comprises strains with heterogeneous virulence capacity, from non-virulent to highly virulent. Determination of the pathogenic potential of the strains is important for diagnosis and disease control. The virulence-associated trimeric autotransporters (vtaA) genes have been used to predict H. parasuis virulence by PCR amplification of their translocator domains. Here, we report a new and improved PCR designed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
65
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(67 citation statements)
references
References 11 publications
2
65
0
Order By: Relevance
“…However, this new PCR still needs further study because only a limited number of non‐pathogenic strains were examined in detail. As well, the non‐pathogenic reference strains for serovars 7 and 11 were apparently virulent in this assay, with one of them being sensitive and one resistant, respectively, in a phagocytosis assay …”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations
“…However, this new PCR still needs further study because only a limited number of non‐pathogenic strains were examined in detail. As well, the non‐pathogenic reference strains for serovars 7 and 11 were apparently virulent in this assay, with one of them being sensitive and one resistant, respectively, in a phagocytosis assay …”
Section: Discussionmentioning
confidence: 68%
“…A UK study that involved whole‐genome sequences of 212 isolates revealed that the group 1 vtaA translocator sequence was found in all isolates; however, there was a difference in the leader sequence of the pathogenic and non‐pathogenic strains . Recently, a PCR was developed for the recognition of potentially virulent strains using a translocator sequence of vtaA . Essentially, those authors argued that VtaA from group 1 does play a role in virulence but that the conditions of a PCR to detect the gene were vital to specificity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, serovar is regarded as a poor proxy for virulence, with the exception of serovars 4 and 5 (12)(13)(14). The vtaA multiplex PCR (mPCR) (15)(16)(17) is the only method that has shown an association between the test result for a given isolate and its virulence, but its wide-scale use has not been reported.…”
mentioning
confidence: 99%